Primary tumour location as a prognostic factor for survival in neuroendocrine tumor in HUSM : 10 years review - Shah, Muhammad Ezzra Shah Rahman (2017)
Background Neuroendocrine tumour is on the rise. The incidents doubled compared to last decade. It presents with a variety of manifestations and sometimes become a challenge to diagnose. Currently, with the modern technology, neuroendocrine tumour (NET) can be detected and managed accordingly. Neuroendocrine tumour is a spectrum of disease which can be managed surgically or non-surgically. It is associated with wide range of symptoms and signs. The most important is the carcinoid syndrome. Sometimes, NETs are found incidentally during routine check-up and imaging. Most of the time, patients presented with evidence of metastasis (stage 4 disease). NETs can be detected using serum chromogranin A. Primary tumour localization can be found using imaging such as CT, MRI or PET scan. It is important to know the primary tumour localization as prognosis is associated with it. Methodology All patients who are diagnosed with neuroendocrine tumour in Hospital Universiti Sains Malaysia from January 2005 to December 2015 are retrospectively reviewed. A total of 48 patients who met the inclusions and exclusion criteria were enrolled for this study. List of the patients is obtained from record office. The medical records of patients that recruited in the study will be reviewed and the data will be entered into the data collection form. The data (age, gender, patient’s symptoms, primary tumour location, surgical information, histopathological examination findings, imaging, biomarkers, stage of disease, and patient’s outcome) will be analysed. Descriptive analysis will be done using mean and standard deviation for numerical variables and frequency and proportion for categorical variables. Result Association of primary tumour location and survival was analysed. Five-years disease free survival in NET according to primary tumor location estimated by Kaplan-Meier analysis. The survival rate was high in tumor in breast ( 85 months) and lower in lung and pleura (9.7 months). The comparisons were significant in all tumor location except in lung, pleura and cervix. The median survival time were high in other tumor location (30.0 months) and lower in unknown location ( 7.0 months). Conclusion Our study demonstrated that primary tumour location is a prognostic factor for survival in neuroendocrine tumour. Primary tumour location in breast, appendix and colorectal have better survival while NET with unknown primary tumour location and in lung or pleura have poor survival.